2014
DOI: 10.1186/2193-1801-3-276
|View full text |Cite
|
Sign up to set email alerts
|

Post-discharge symptoms following fast-track colonic cancer surgery: a phenomenological hermeneutic study

Abstract: ObjectiveTo obtain knowledge of patients’ experiences of postoperative symptoms during the initial two weeks following fast-track colonic cancer surgery.MethodSemi-structured in-depth interviews with seven colonic cancer patients two weeks post hospital discharge. Analysis was performed using a phenomenological hermeneutical approach.ResultsDuring the first two weeks after discharge the patients experienced unfamiliar symptoms that affected their everyday lives. Despite distressing symptoms, they applied a “wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(67 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…When recovery did not proceed as expected, participants in the study by Beech et al (2012) doubted the validity of their concern due to their lack of experience or knowledge. A strategy of 'wait and see' has been described in studies because participants hesitate to contact healthcare professionals as they believe that their symptoms will eventually disappear or that they are not important enough to warrant contact (Beech et al, 2012;Krogsgaard, Dreyer, Egerod, & Jarden, 2014). It has also been reported that participants do not know what to expect after coming home from hospital, which leads to anxiety and concern (Beaver et Taylor et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…When recovery did not proceed as expected, participants in the study by Beech et al (2012) doubted the validity of their concern due to their lack of experience or knowledge. A strategy of 'wait and see' has been described in studies because participants hesitate to contact healthcare professionals as they believe that their symptoms will eventually disappear or that they are not important enough to warrant contact (Beech et al, 2012;Krogsgaard, Dreyer, Egerod, & Jarden, 2014). It has also been reported that participants do not know what to expect after coming home from hospital, which leads to anxiety and concern (Beaver et Taylor et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These values are also reflected in the ideals of patient participation and correspond with values of an ethics‐of‐care perspective that emphasizes the specific needs of specifics individuals in specific situations as reflected by important nurse theorists such as (Benner & Wrubel, ; Martinsen & Eriksson, ; Travelbee, ). Empirical studies dealing with patients’ experiences of participating in fast‐track programmes and evidence‐based practices send similar messages (Kovarsky, ; Krogsgaard et al., ; Norlyk & Harder, ; ). No one wants to be a ‘hip replacement’.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous phenomenological research of patients’ experiences of participating in fast‐track programmes has illustrated a clinical practice dominated by the rationality of scientific evidence (Krogsgaard, Dreyer, Egerod, & Jarden, ; Norlyk & Harder, ; ; Norlyk & Martinsen, ). Drawing on our previous research, we provide an exemplary narrative of how evidence‐based programmes are being practised in Danish hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast-track programmes in Denmark are usually organised with follow-up contact for the patients after discharge (Kehlet 2011;Hjort Jakobsen et al 2014); however, follow-up was not performed for the patients in the present study. Research showed that patients may be hesitant or uncomfortable about asking questions or requesting additional information for fear of taking up too much time, appearing uninformed, feeling that they are a bother, are unaware of available options or because they do not know who to ask for help (Parker & Kreps 2005;Steele & Fitch 2008;Krogsgaard et al 2014). This indicates that follow-up contact in the week following discharge should preferably be the responsibility of health professionals, and may be required for patients after surgical treatment for lung cancer.…”
Section: Discussionmentioning
confidence: 99%